Does Hinduism lack social concern? - Nadkarni, M.V. (2007)
Though secular institutions and the state have emerged as major agents of social concern and development, it is still useful to highlight the humanist role of religion in these areas. By stressing humanism and social concern as the core of religion, parochial tendencies that could lead to violence may be checked. How far does Hinduism have social concerns? This issue is examined in this article both at the level of theory or doctrine and actual practice. - Reproduced.
Keywords: Hinduism